(untitled) (International Journal of Physiotherapy, 2014)
Background: Chronic obstructive pulmonary disease (COPD) is the only cause of death from chronic disease that will increase worldwide until 2020 and it represents a big burden for patients and society. Patients with COPD characteristically show poor exercise performance indicated by a marked reduction in both peak pulmonary 02 uptake and work rate at peak exercise. The sequelae of exercise intolerance include increased difficulty in performing daily tasks, etc. The objective of the study is to investigate the influence of thoracic and upper limb muscle function on 6-min walk distance (6MWD) in patients with COPD. Method: Thirty eight COPD patients were included if they fulfilled the criteria for COPD according to the Global Initiative for Chronic Obstructive Lung Disease guidelines. Prospective, cross-sectional design with sample size of 38 patients. All patients performed 6MWD and 1RM exercises. Results: To study the correlation between variables, Pearson or Spearman coefficients of correlation were used with the level of statistical significance set at 5%.Results of this study suggested for the first time that thoracic muscle strength is a predictor of 6MWD in COPD patients. It also confirms the influence of respiratory muscle strength (Pimax), dyspnea, on the 6MWD of these patients. Conclusion: It is concluded that peripheral muscle strength, respiratory muscle strength, and the sensation of dyspnea all have an influence on the capacity of COPD patients to perform exercises.